THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR), CAPITAL STRUCTURE, AND DIVIDEND POLICY ON COMPANY VALUE IN ENERGY SECTOR COMPANIES - Awanda Novi Cahyawati; Sri Suryaningsum (CV. Fahr Publishing, 2024)
This study aims to empirically test the effect of corporate social responsibility (CSR), capital structure, and dividend policy on company value in energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This study uses the latest GRI standard, namely 101, which replaces the GRI standard 304 regarding biodiversity, so that it is expected to provide a more accurate assessment of the company's CSR, especially regarding environmental aspects, especially biodiversity. This study uses a sample of 120 consisting of 38 companies obtained based on the purposive sampling method. The data used in this study are secondary data consisting of annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange and the company's official website. This study uses multiple linear regression analysis techniques. The results of this study indicate that CSR and capital structure do not affect company value. CSR and capital structure require costs for long-term projects and sustainability in the energy sector, so their impact on company value cannot be felt directly. Meanwhile, dividend policy has a positive effect on company value. Investors prefer dividend rewards obtained in the short term.